Nanotechnology-based Colorimetric Approaches for Pathogenic Virus Sensing: A Review - Filik, Hayati; Avan, Asiye Aslıhan (Current Medicinal Chemistry, 2022)
Fast and inexpensive virus identification protocols are of paramount value to hinder the increase of pandemic diseases, minimize economic and social damages, and expedite proper clinical rehabilitation. Until now, various biosensors have been developed for the identification of pathogenic particles. But, they offer many limitations. Nanotechnology overcomes these difficulties and allows a direct identification of pathogenic species in real-time. Among them, nanomaterial based-colorimetric sensing approach for identifying pathogenic viruses by the naked eye has attracted much awareness because of their simplicity, speed, and low cost. In this review, the latest tendencies and advancements used in detecting pathogenic viruses using colorimetric concepts, are overviewed. We focus on and reconsider the use of distinctive nanomaterials such as metal nanoparticles, carbon nanotubes, graphene oxide, and conducting polymer for the formation of colorimetric pathogenic virus sensors.
Keywords: detection